2009
DOI: 10.1128/mcb.00042-09
|View full text |Cite|
|
Sign up to set email alerts
|

A Mouse PRMT1 Null Allele Defines an Essential Role for Arginine Methylation in Genome Maintenance and Cell Proliferation

Abstract: Protein arginine methyltransferase 1 (PRMT1) is the major enzyme that generates monomethylarginine and asymmetrical dimethylarginine. We report here a conditional null allele of PRMT1 in mice and that the loss of PRMT1 expression leads to embryonic lethality. Using the Cre/lox-conditional system, we show that the loss of PRMT1 in mouse embryonic fibroblasts (MEFs) leads to the loss of arginine methylation of substrates harboring a glycine-arginine rich motif, including Sam68 and MRE11. The loss of PRMT1 in MEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
169
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 69 publications
9
169
0
2
Order By: Relevance
“…Measuring the level of Axin in cell lines stably expressing PRMT1 shRNA revealed an obvious correlation between the level of Axin and PRMT1 (Figure 4b and Supplementary Figure 4F). To further confirm the role of PRMT1 in the stabilization of Axin, we have used the embryonic fibroblast cell line PRMT1 FL/-;CreERT MEF established from a conditional knockout mouse, in which PRMT1 was deleted by the addition of 4-hydroxytamoxifen (Yu et al, 2009). The level of endogenous Axin or ectopically expressed Myc-Axin was clearly reduced in 4-hydroxytamoxifentreated cells whereas the level of co-transfected green fluorescent protein (GFP) was not changed (Figure 4c).…”
Section: Prmt1 Methylates Axin In Vivomentioning
confidence: 97%
See 1 more Smart Citation
“…Measuring the level of Axin in cell lines stably expressing PRMT1 shRNA revealed an obvious correlation between the level of Axin and PRMT1 (Figure 4b and Supplementary Figure 4F). To further confirm the role of PRMT1 in the stabilization of Axin, we have used the embryonic fibroblast cell line PRMT1 FL/-;CreERT MEF established from a conditional knockout mouse, in which PRMT1 was deleted by the addition of 4-hydroxytamoxifen (Yu et al, 2009). The level of endogenous Axin or ectopically expressed Myc-Axin was clearly reduced in 4-hydroxytamoxifentreated cells whereas the level of co-transfected green fluorescent protein (GFP) was not changed (Figure 4c).…”
Section: Prmt1 Methylates Axin In Vivomentioning
confidence: 97%
“…PRMT1 has an essential, non-redundant role in embryonic development, as PRMT1À/À embryos die shortly after implantation (Pawlak et al, 2000). A conditional PRMT1 knockout in mouse embryonic fibroblasts showed that PRMT1 is required for cell proliferation and DNA damage response signaling (Yu et al, 2009). Moreover, arginine methylation by PRMT1 has been implicated in a variety of processes such as signal transduction, protein trafficking, transcriptional regulation, DNA repair and protein-protein interactions (McBride and Silver, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Protease inhibitor cocktail and protein phosphatase inhibitor cocktail were from Roche (Mississauga, ON, USA). CHK1 substrate peptide (KKKVSRSGLYRSPENLNRPR) derived from Immunoprecipitations and immunoblotting were performed as previously described [5].…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…PRMT1-null mice are embryonically lethal and contain numerous hypomethylated substrates [4]. Using a conditional null PRMT1 allele in mice, it was shown that PRMT1-deficient mouse embryonic fibroblasts (MEFs) exhibit spontaneous DNA damage, chromosome instability, polyploidy and defective checkpoint activation following DNA damage [5]. These findings highlight the importance of arginine methylation in the DNA damage response pathway and the maintenance of genomic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies reported that PRMT1 was associated with the inhibition of proliferation and apoptosis induction in lung cancer and gliomas [15,16]. On the other hand, PRMT1 inhibition was reported to induce suppression of the proliferation potency of bladder and lung cancer cells [17] and enhanced chemosensitivity via inhibition of DNA repair in osteosarcoma cells [18]. These data suggested that PRMT1 plays various important roles in several types of cancer cells.…”
Section: Introductionmentioning
confidence: 96%